Improving the Solar Panel Efficiency by Using Cooling and Cleaning Techniques: Improving the Solar Panel Efficiency by Using Cooling and Cleaning Techniques (Journal of University of Babylon for Engineering Sciences, 2017)
This paper is a contribution to research work which aims at ending the electricity crisis in Iraq. The electric power stations, which use conventional fuel, are unable to provide the growing population with electricity all day-long. Moreover, electric distribution lines are sometimes exposed to attacks by terrorists.This paper recommends solar energy as the optimum solution to the electricity problem in Iraq, since it is both renewable and friendly to the environment.The paper also concentrated on reliability techniques to improve the efficiency of the solar energy system. This was achieved by means of designing and constructing a cooling system that consists of fans, sprinklers and wipers to eliminate excessive heat from solar panels when temperature rises to maximum levels. Sprinklers and wipers are also useful for cleaning the panels because dust is a negative factor which undermines the generation capacity of solar panels.  The cooling system is operated by means of a microcontroller that is programmed through Proteus 8, Arduino, and Matlab2016. Statistics reveal that a cooling system has significantly improved the productive capacity of the solar system and it can achieve an energy gain of (34.55%).